Comparison of Treatment Outcomes of Intravenous versus Intra-arterial Chemotherapy in Retinoblastoma - Muhammad Usman; Fauzan, Ahmad; Arslan, Ahmed; Gul, Raheem (Indus Journal of Bioscience Research, 2025)
Background: Retinoblastoma is the most common intraocular malignancy in children. While systemic intravenous chemotherapy (IVC) has improved outcomes, responses remain suboptimal in advanced disease. Intra-arterial chemotherapy (IAC) offers targeted drug delivery, but direct comparative evidence remains limited in resource-constrained settings. Objective: To compare treatment outcomes of IVC versus IAC in patients with retinoblastoma. Methods: A quasi-experimental study was conducted at the Department of Ophthalmology, Lahore General Hospital, from July 2024 to June 2025. Ninety-two children with newly diagnosed intraocular retinoblastoma (stages B-E) were randomized into two groups of 46 patients each. Group A received systemic IVC with vincristine, etoposide, and carboplatin. Group B received IAC with melphalan, with topotecan or carboplatin added for resistant disease. Tumor response was assessed according to WHO Response Evaluation Criteria. Data were analyzed using chi-square test with significance at p